A New Piece of the Puzzle to Understand Cervical Sagittal Alignment: Utilizing a Novel Angle δ to Describe the Relationship among T1 Vertebral Body Slope, Cervical Lordosis, and Cervical Sagittal Alignment. Issue 3 (29th March 2019) - Goldschmidt, Ezequiel; Angriman, Federico; Agarwal, Nitin; Trevisan, Marcos; Zhou, James; Chen, Katherine; Gerszten, Peter C; Kanter, Adam S; Okonkwo, David O; Passias, Peter; Scheer, Justin; Protopsaltis, Themistocles; et al.
Abstract: Cervical alignment has become increasingly important in the planning of spine surgery. A relationship between the slope of T1 (T1S), the cervical lordosis (CL), and the overall cervical sagittal vertical axis (cSVA) has previously been demonstrated, but the exact nature of this relationship is poorly understood. In this study, we derive theoretical and empirical equations to better understand how T1S and CL affect cSVA. The first equation was developed on a theoretical basis using inherent trigonometric relationships of the cervical spine. By treating the cervical spine as the arc of a circumference, and by taking into account the cervical height (CH), the geometric relationship between theT1S, CL, and cSVA was described via a trigonometric identity utilizing a novel angle δ subtended by the CH and cSVA (δ = T1S-CL/2). The second equation was developed on an empiric basis by performing a multiple linear regression on data obtained from a retrospective review of a large multicenter deformity database. The theoretical equation determined that the value of cSVA could be expressed as: cSVA = CH*tan( π /180*( T1S - CL/2 ) ) . The empirical equation determined that value of cSVA could be expressed as: cSVA=(1.1*T1 ) - ( 0.43*CL ) + 6.69 . In both, the sagittal alignment of the head over the shoulders is directly proportional to the T1S and inversely proportional to CL/2. These 2 equations may allow surgeons to better understand how the CL compensates for the T1S, to accurately predict the postoperative cSVA, and to customize cervical interbody grafts by taking into consideration each individual patient's specific cervical spine parameters.